HISTORIOGRAPHY OF THE HISTORY OF CONVENIENT AND FOOD INDUSTRY (TAMADDUN NURI JURNALI, 2024)
As a result of the reforms carried out in the Republic of Uzbekistan, the effectiveness of scientific research is also increasing. Scientific research works, monographs and manuals dedicated to the study of the history of the light and food industry are among them.